Leadership competencies at MTBE (M) Sdn Bhd : a case study - Foo, Muhammad Furqan Abdullah (2008)
The research objectives was to determine what is the level of leadership competencies of the El and E2 executives and the significance of the leadership competencies model being employed by the organizations. The methodology used was through references to previous studies and theories with regards to leadership competencies required in an organization and via analysis on the data collected from the organization in accordance to the theoretical framework employed. The four (4) leadership dimensions studied was Behaves as Owner, Outperforms, Inspires Followers and Develops People. Through the analysis, it was found out that the majority of the executives in the organizations felt that they possessed a high level of leadership competencies. However, the results of the leadership competencies model and the dimensions studied only showed 65% significance level. In conclusion, the significance is not profound between the leadership dimensions and leadership competencies, The organization may need to rethink and re-strategize if necessary, which Leadership Dimension that they would want their executives to be proficient in and also maybe to limit the number of dimensions that their executives needs to be competent in. (Author's abstract)